PENGARUH CONTENT MARKETING DAN BRAND AWARENESS TERHADAP KEPERCAYAAN GUNA MENINGKATKAN KEPUTUSAN PEMBELIAN - Leonita Ristiani; Adi Sismanto (UM. Bengkulu, 2026)
This study aims to analyze the influence of content marketing and brand awareness on trust in order to increase purchasing decisions for Skintific skincare among Generation Z. Case study: Pematang Gubernur sub-district. Data was analyzed using path analysis to test the direct and indirect relationships between the independent variables (content marketing and brand awareness), the mediating variable (trust), and the dependent variable (purchase decision). The problems found in this study are consumer dissatisfaction with Skintific products due to overly high expectations from content marketing promotions on social media, product incompatibility with some consumers causing irritation, relatively higher product prices compared to other brands, and fierce competition in the skincare industry. Although Skintific's brand awareness is quite strong, it has not been able to fully increase the trust and purchasing decisions of Generation Z consumers. The results show that Content Marketing and Brand Awareness have a positive and significant effect on trust, with path coefficients of 0.880 and 0.815, respectively. Additionally, trust acts as a significant mediating variable in increasing the purchase decision for Skintific skincare. Content Marketing and Brand Awareness have also been proven to have an indirect influence on purchasing decisions through trust, with coefficients of 0.879 and 0.801, respectively. Trust in skincare skintific purchasing decisions among Generation Z in Pematang Gubernur Village has a coefficient of 0.890 or 89% with a significance level of 0.000 < 0.050, so Ho is rejected. Keywords: Content Marketing, Brand Awareness, Trust, Purchase Decision